EFISIENSI PEMBERIAN PUPUK KOTORAN KAMBING UNTUK PEMBIBITAN PENAGE (Calophyllum inophyllum Linn) - Wulandari, Intan; Muin, abdurrani; M, Iskandar A (Universitas Tanjungpura, 2017)
Penage (Calophyllum inophyllum Linn) is one type of alternative forest fuel crops (biofuel). The natural regeneration condition of penage that decreases requires cultivation development effort. This research aimed to detecting effect and dose giving of goat manure which appropriative to produce good quality penage seedling. The method used is the experimental method with Completely Randomized Design. Treatment of goat manure dose is 0 gram/polybag, 50 gram/polybag, 150 gram/polybag, 250 gram/polybag and 350 gram/polybag. Parameters observed were height, diameter, amount of leaves, total dry matter, top and root ratio and seedling quality index. The results showed goat manure gave significantly effected on increase height and diameter penage seedling at 14 weeks. While on the amount of leaves, total dry matter, top and root ratio and seedling quality index not significant. Application of goat manure with a dose of 250 gram/polybag is an efficient dose to increase penage growth and is recommended for penage seedling activities.KeywordsÂ Â : Eficiency, goat manure, growht, penage